Одоление: [сборник стихов] / Виталий Ложкин - Ложкин Виталий Артемьевич (Сарапульская городская типография, 2006)
Экземпляры: (20160212) / Инвентарный номер: 1938 / Сис.шифр: Р2 / Авт.знак: Л 71 / ГРНТИ: 17 / ББК: 84(2)